A Qualitative Investigation of College Students' Facebook Usage and Romantic Relationships: Implications for College Counselors. Issue 2 (1st July 2016) - Sherrell, Renee S.; Lambie, Glenn W.
Abstract : The use of social media is a societal trend influencing the way that individuals communicate with and relate to one another. Moreover, Facebook use may facilitate or hinder individuals' relationship growth and development. The purpose of this article is to (a) review research examining Facebook usage and interpersonal relationships, (b) present qualitative insight into the Facebook experiences of college students ( N = 16) from a large southeastern university, and (c) offer implications for college counselors.